From Data to Policy: Database-Policy Making in the Case of Civil Service in Ngepung, Ngantuk - P.F. Nuryananda; B. Prabowo; Suwandi (Nusantara Science and Technology Proceedings)
Ngepung Village, Nganjuk District, is a village that is geographically located at the intersection of the Nganjuk, Jombang and Lamongan regions. Ngepung village has a dry type of soil because the village land is lime-mixed clay. This condition causes rainwater cannot be absorbed properly by the land of Ngepung Village. As a result, the village is experiencing drought and lack of water. With the background of the village conditions, the implementing team is engaged in activities to provide alternative solutions to help overcome village problems. However, in starting to provide alternative solutions, the implementing team used a quantitative approach, namely the use of a database on population and village potential. To get and use the database at the same time as the basis for providing alternative solutions, the community service team used the Village Build Index (Indeks Desa Membangun/IDM) questionnaire by the Ministry of Villages, Development of Disadvantaged Regions and Transmigration (Kementerian Desa, Pembangunan Daerah Tertinggal, dan Transmigrasi). With the use of IDM as an instrument of research as well as community service, the pattern of the life of the Ngepung Village community will be mapped. The mapping results by IDM can simultaneously help the village to complete village data so that the village also benefits administratively by the existence of this community service. The fact is that the people of Ngepung Village experienced several conditions, including 1) still dependent on forest products, 2) there were still many who did not have latrines, and 3) there were still many who did not use livestock manure.